Kemampuan Siswa Kelas Vll SMP Negeri 1 Runjung Agung Mengubah Teks Wawancara Menjadi Narasi Menggunakan Model Pembelajaran Siklus - Inawati, Inawati; Agustina, Aryanti; Awalludin, Awalludin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2024)
This research was conducted to describe the results of class Vll students' ability at SMP Negeri 1 Runjung Agung to change interview texts into narratives using the Cycle Learning Model. The research method used is quantitative and data collection techniques are carried out using test techniques. The sample was class Vll.l, totaling 31 people. Based on the research results, the ability of class Vll students at SMP Negeri 1 Runjung Agung OKU Selatan to change interview text into narratives using the Cycle Learning Model is in the good category. This is aimed at the test results of students who got a score of 85 there were 2 people (6.45%), who got a score of 80 there were 4 people (12.9%), who got a score of 75 there were 7 people (22.5%), who 7 people got a score of 70 (22.5%), 2 people got a score of 65 (6.4%), and 9 people got a score of 60 (29.0%). The results of calculating the average score of students changing interview text into narratives using the Cycle Learning Model reached 70.2 in the good category. Thus, it can be concluded that the lesson on changing interview text into a narrative for class V of SMP Negeri 1 Runjung Agung OKU Selatan was successfully implemented and the Cycle Learning Model was effectively used in the lesson.